ChemInform Abstract: Synthesis, Evaluation of Insecticidal Activity, and Crystal Analysis of cis‐Nitenpyram Analogues Bearing 1, 4‐Dihydropyridine. Issue 42 (1st October 2013) - Sun, Chuanwen; Liu, Tianyan; Ding, Li; Chen, Yanxia; Zhang, Wanggeng
Abstract Title compounds (IV) are synthesized by multicomponent reactions and evaluated for their insecticidal activity against Aphis medicagini.